The Politics of nature : explorations in green political theory - Dobson, Andrew; Lucardie, Paul, 1946- (Routledge, 1993)
A balanced and comprehensive survey of current green political ideas - their varying responses to fundamental problems in political theory and their relationships with other ideological traditions.